A rare case of localized peliosis hepatis during adjuvant chemotherapy including oxaliplatin mimicking a liver metastasis of colon cancer - Akira Dejima; Yasuji Seyama; Daisuke Nakano; Misato Takao; Soichiro Natsume; Mikiya Takao; Sakiko Nakamori; Tatsuya Kanai; Shinichiro Horiguchi; Kazushige Kawai (Surgical Case Reports, 2023)
Abstract Background Oxaliplatin-based regimens are commonly used as adjuvant chemotherapy following surgery for colorectal cancer. Adverse events associated with oxaliplatin include blue liver, which is caused by sinusoidal dilation and diffuse peliosis hepatis. We report herein a case of localized peliosis hepatis closely resembling a metastatic liver tumor. Case presentation The patient, a 50-year-old male, underwent a robotically assisted colectomy for rectosigmoid colon cancer, which was discovered when hematochezia occurred. The patient received a diagnosis of pStage IIIb and was treated with four courses of CAPOX as adjuvant chemotherapy starting at postoperative month 1. At postoperative month 4, contrast-enhanced computed tomography (CT) of the abdomen revealed a 20-mm, low-density area with heterogeneous internal structure in S6/7 of the liver. Abdominal ultrasound and gadolinium ethoxybenzyl-diethylenetriaminepentaacetic acid-enhanced magnetic resonance imaging (EOB-MRI) findings led to a diagnosis of metastatic liver tumor, for which a laparoscopic partial hepatectomy was performed. The resected lesion was a dark reddish-brown nodule with indistinct margins that appeared to be continuous with the surrounding area. Histopathological analysis revealed severe, localized dilatation of the sinusoids and congestion consistent with the gross nodule. Based on these findings, localized peliosis hepatis associated with oxaliplatin-induced sinusoidal damage was diagnosed. Conclusions Localized peliosis hepatis associated with oxaliplatin use can be difficult to distinguish from a metastatic liver tumor on imaging studies.